REVIEW LITERATURE: INOVASI ADMINISTRASI KEPROTOKOLAN DALAM PERSPEKTIF E-GOVERNMENT - Almazy, Muhammad Tsaqib; Sugiyanto, Sugiyanto (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The development of information technology has encouraged local governments to innovate in the implementation of public administration, including in the field of protocol administration. Conventional protocol administration practices are often considered insufficient in responding to demands for efficiency, accuracy, and service transparency. This article aims to examine and reflect on innovations in protocol administration from an e-government perspective based on findings from previous studies. This study employs a qualitative literature review method by analyzing relevant national and international journal articles published between 2019 and 2024. The literature was collected from reputable academic databases and analyzed thematically to identify patterns, trends, and key issues. The findings indicate that digital-based protocol administration innovations contribute to improved work efficiency, better inter-unit coordination, and more orderly implementation of governmental activities. Nevertheless, the implementation of such innovations still faces several challenges, including limitations in human resources, resistance to organizational change, and inadequate technological infrastructure readiness. The study concludes that the success of protocol administration innovation is not solely determined by technological factors but also by organizational support, leadership commitment, and bureaucratic work culture. This article is expected to provide a conceptual reference for policymakers and practitioners in developing protocol administration innovations within local government institutions. ABSTRAK Perkembangan teknologi informasi mendorong pemerintah daerah untuk melakukan inovasi dalam penyelenggaraan administrasi publik, termasuk pada bidang keprotokolan. Administrasi keprotokolan yang selama ini bersifat manual dinilai kurang responsif terhadap tuntutan efektivitas, akurasi, dan transparansi layanan. Artikel ini bertujuan untuk mengkaji dan merefleksikan inovasi administrasi keprotokolan dalam perspektif e-government berdasarkan temuan-temuan penelitian terdahulu. Penelitian ini menggunakan metode review literatur kualitatif dengan menelaah artikel jurnal nasional dan internasional yang relevan dan dipublikasikan dalam kurun waktu 2019–2024. Literatur dikumpulkan melalui basis data ilmiah terpercaya dan dianalisis secara tematik untuk mengidentifikasi pola, kecenderungan, serta isu utama yang berkembang. Hasil kajian menunjukkan bahwa inovasi administrasi keprotokolan berbasis digital berkontribusi terhadap peningkatan efisiensi kerja, kualitas koordinasi antarunit, serta ketertiban pelaksanaan kegiatan pemerintahan. Namun demikian, implementasi inovasi tersebut masih menghadapi berbagai tantangan, seperti keterbatasan sumber daya manusia, resistensi terhadap perubahan, serta kesiapan infrastruktur teknologi. Simpulan dari kajian ini menegaskan bahwa keberhasilan inovasi administrasi keprotokolan tidak hanya ditentukan oleh aspek teknologi, tetapi juga oleh dukungan organisasi, kepemimpinan, dan budaya kerja birokrasi. Artikel ini diharapkan dapat menjadi rujukan konseptual bagi pengembangan kebijakan inovasi keprotokolan di pemerintah daerah.